Case Report: Clinical Remission in a Cat With Severe Bilateral Eosinophilic Keratitis Receiving Combined Immunosuppressive Therapy (Triamcinolone Acetonide and Tacrolimus) - Romaneck, Amanda K.; Sebbag, Lionel (Frontiers in Veterinary Science, 2021)
A 2-year old domestic shorthair cat was examined for severe keratitis of 10 months duration, non-responsive to 0.1% dexamethasone q8-12h. Patient and owner compliance were poor given ocular discomfort and hiding behavior. On presentation, both eyes (OU) had severe ulcerative keratitis that masked examination of deeper structures and resulted in absent menace response OU. Corneal cytology was consistent with eosinophilic keratitis OU. Initial therapy included subcutaneous triamcinolone acetonide injection (0.2 mg/kg), 0.3% ciprofloxacin OU q12h, and two compounded drugs started 5 days later upon receipt: 0.5% tacrolimus OU q6h, 0.5% cidofovir OU q12h. Visual behavior and ocular comfort were reportedly much improved within 24 hours. At the first recheck (Day 11), patient and owner compliance were reported to be excellent, menace response was positive OU and keratitis was dramatically reduced OU with absent fluorescein uptake. Subcutaneous triamcinolone acetonide was repeated (0.2 mg/kg), ciprofloxacin was discontinued, cidofovir was continued q12h and tacrolimus was slowly tapered (q8h x3 weeks then q12h). Keratitis was nearly 100% resolved at the second recheck (Day 38); cidofovir was discontinued and tacrolimus was slowly tapered (q12h x1 week, q24h x4 weeks, q48h x4 weeks) then discontinued. A third recheck (Day 101) confirmed clinical remission OU, and disease did not reoccur within a 1 year follow up period (photographic documentation by owner). In sum, adjunct use of triamcinolone acetonide greatly improved therapeutic compliance and helped control severe eosinophilic keratitis in a rapid and effective manner.